Cover Picture: Electrochemically Mediated Atom Transfer Radical Polymerization from a Substrate Surface Manipulated by Bipolar Electrolysis: Fabrication of Gradient and Patterned Polymer Brushes (Angew. Chem. Int. Ed. 13/2015). Issue 13 (6th March 2015) - Shida, Naoki; Koizumi, Yuki; Nishiyama, Hiroki; Tomita, Ikuyoshi; Inagi, Shinsuke
<x xml:space="preserve">Abstract</x> Gradient growth of poly(NIPAM) brushes from an initiator‐modified substrate surface was achieved by electrochemically mediated atom‐transfer radical polymerization (eATRP). In their Communication on page 3922 ff., S. Inagi et al. show that setting the surface close to a bipolar electrode results in a potential gradient, which leads to a concentration gradient of the CuI polymerization catalyst on the substrate. The polymer brushes could be fabricated in three‐dimensional gradient shapes with control over thickness, steepness, and modified area.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>